PROTOTYPING PENGENDALI DAN MONITORING SISTEM IRIGASI GUNA MENCEGAH PENCURIAN AIR DIWILAYAH KECAMATAN JETIS - Gumelar, Satrio Suryo; Kurniawan, Edy; Habiby, Jawwad Sulthon (Universitas Muhammadiyah Ponorogo, 2021)
Water is a very important element in human and plant life. The dry season makes the amount of water supply dwindling, this has an impact on farmers' yields to decline. Limited water from rivers makes farmers unable to meet the needs of crops and agricultural areas. Irrigation from rivers is often a social conflict that often occurs in the community because of the problem of water distribution that is not controlled. The huge water demand for farmers demands a water treatment system. Thus the irrigation system becomes a very important support for the smoothness and success of agricultural products, especially the agriculture of the Turi Village community, Jetis District. The design of this irrigation system controller and monitoring prototype uses an Arduino Mega based on NodeMCU (ESP 8266) as a system controller. The process of distributing river water which was previously done manually is replaced by using an automatic system that can be monitored via the telegram application. All components are controlled by arduino mega as a command interpreter from the user. Users can control the prototype using commands from the Telegram application installed on Android and IOS devices. The opening height of the irrigation door can be adjusted by the user. When there is an overflow of water in the river, the system will open all the floodgates automatically so that there is no flood. Based on the tests that have been carried out, the results obtained are that the JSN-SR04T proximity sensor will measure the water level of the river, if the water level exceeds the limit, the user will receive a notification via the telegram application and all floodgates will open automatically. When the sluice gate is forcibly opened, the user will receive a notification via the telegram application and the buzzer installed on the system will sound.Â